Identificacion de nematodos asociados con pitaya Acanthocercus pitahaya Jaq. Dugand - Castaño, S.P.=700 1 Rincon, A.; Varon de Agudelo, F.
(En, Es)
ilus., 17 ref.
Keywords: IDENTIFICACION; NEMATODA; MELOIDOGYNE; HELICOTYLENCHUS; TYLENCHORHYNCHUS; HYLOCEREUS UNDATUS; COLOMBIA; PITAHAYA